2002
DOI: 10.1038/sj.ijir.3900887
|View full text |Cite
|
Sign up to set email alerts
|

Penile length is normal in most men seeking penile lengthening procedures

Abstract: Concerns over penile size and a desire for a longer penis are common in the male population. The number of male patients seeking an andrological consultation for the problem of 'short penis' is increasing. We looked at the numbers of patients presenting to a University andrology clinic over a 2-y period and correlated their perceived penis size with the accepted norms. Sixty-seven patients were evaluated with a median age of 27 (range 16 -55) complaining of 'short penis' and requesting surgical correction. Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
129
0
10

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(143 citation statements)
references
References 7 publications
4
129
0
10
Order By: Relevance
“…Mondaini et al 2 reported that most men who seek penile lengthening surgery 'overestimate' the 'normal' penile length. In their study of 67 patients complaining of 'short penis', none were found to be having a severely short penis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mondaini et al 2 reported that most men who seek penile lengthening surgery 'overestimate' the 'normal' penile length. In their study of 67 patients complaining of 'short penis', none were found to be having a severely short penis.…”
Section: Discussionmentioning
confidence: 99%
“…The definition of normal penile size has become more significant in the context of increasing demand for penile augmentation. [1][2][3][4] Data on normal size of penis will help (1) to perform correct diagnostic assessment and therapeutic choices, (2) to educate and counsel the patients with concerns about 'penile size adequacy', and (3) to manufacture condoms with correct size. 5 Previous studies on phallic dimensions (Table 1) are limited and there is a wide difference in methodology.…”
Section: Introductionmentioning
confidence: 99%
“…2 Concerns over penile size and a desire for a longer penis are common in the male population and the number of male patients seeking andrological consultation for the problem of 'short penis' is increasing. 3 Most commonly these patients are otherwise physically normal males, who seek validation of their sexual function and fertility potential, true confirmation of genital organ normality and adequacy. Furthermore, the definition of normal penile size is currently of considerable importance in the diagnosis and treatment of sexual dysfunction and in the light of the claims of penile augmentation in the lay press.…”
Section: Introductionmentioning
confidence: 99%
“…6 However, most of the men (or parents bringing children) seeking help for "small penises" do not really present abnormal penis sizes. 6,7 They are just esthetically dissatisfied, 6 and many surgery clinics (urology and plastic) are probably profiting from this dissatisfaction. While this is an issue still under investigation, this complaint has already being named in the literature as "penis dysmorphophobia", 3,6,7 a condition in which men seek medical treatments believing that their penises are too short.…”
Section: Introductionmentioning
confidence: 99%